2004
DOI: 10.1038/sj.cr.7290231
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of human ACAT1 gene expression to promote the macrophage-derived foam cell formation by dexamethasone

Abstract: In macrophages, the accumulation of cholesteryl esters synthesized by the activated acyl-coenzyme A:cholesterol acyltransferase-1 (ACAT1) results in the foam cell formation, a hallmark of early atherosclerotic lesions. In this study, with the treatment of a glucocorticoid hormone dexamethasone (Dex), lipid staining results clearly showed the large accumulation of lipid droplets containing cholesteryl esters in THP-1-derived macrophages exposed to lower concentration of the oxidized low-density lipoprotein (ox-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 38 publications
3
61
0
Order By: Relevance
“…Human THP-1 monocytes were adhered on cover slips in a 12-well plate with treatment of 1 mM ATRA or ATRA plus TNFa in the RPMI 1640 medium supplemented with 10% FBS for 40 h; for the NF-kB inhibition assay, the inhibitor PGA1 was added to the medium prior to stimulation of TNFa. Then the cells were cultured with oxidized low-density lipoproteins (oxLDL; 40 mg/ml), which are prepared as described (24,25) but without TNFa, for another 48 h in the fresh RPMI 1640 medium containing 10% lipoprotein-deficient serum (LPDS). For the ACAT inhibition assay, the ACAT inhibitor CP-113,818 was added to the fresh RPMI 1640 medium containing 10% LPDS and oxLDL (40 mg/ml) after stimulation of TNFa.…”
Section: Cell Culturementioning
confidence: 99%
“…Human THP-1 monocytes were adhered on cover slips in a 12-well plate with treatment of 1 mM ATRA or ATRA plus TNFa in the RPMI 1640 medium supplemented with 10% FBS for 40 h; for the NF-kB inhibition assay, the inhibitor PGA1 was added to the medium prior to stimulation of TNFa. Then the cells were cultured with oxidized low-density lipoproteins (oxLDL; 40 mg/ml), which are prepared as described (24,25) but without TNFa, for another 48 h in the fresh RPMI 1640 medium containing 10% lipoprotein-deficient serum (LPDS). For the ACAT inhibition assay, the ACAT inhibitor CP-113,818 was added to the fresh RPMI 1640 medium containing 10% LPDS and oxLDL (40 mg/ml) after stimulation of TNFa.…”
Section: Cell Culturementioning
confidence: 99%
“…Moreover, several authors showed that dexamethasone (DXM, 1mM) (a synthetic GC receptor agonist) could promote the macrophage-derived foam cell formation (a hallmark of early atherosclerotic lesions [738,739] ) at lower concentration of ox-LDL in vitro, and that the drug increased the formation of CEs in macrophages and human SMCs in a dosedependent manner [201,740] . The finding that DXM could promote the foam cell formation at lower ox-LDL concentration might be partially caused by the up-regulation of ACAT1 gene expression at the transcriptional level and the enhancement of cholesterol esterification [194] .…”
Section: Cathepsin Proteasementioning
confidence: 99%
“…GCs not only down-regulated proinflammatory cytokines, they also generated a functionally active, antiinflammatory phenotype in human monocytes that suppressed inflammatory processes and, thus, induced resolution of inflammation [733] . Many studies provided the experimental and clinical evidence that treatment with GCs accelerated and/or exacerbated development of atherosclerosis [194,734,735] . Accumulating evidence had demonstrated that foam cells were formed from macrophages in vitro at high concentrations (80-160 mg/mL) of oxLDL [736,737] .…”
Section: Cathepsin Proteasementioning
confidence: 99%
See 1 more Smart Citation
“…Although ACAT1 is a critical component of intracellular cholesterol homeostasis, its expression is not known to be regulated by the SREBPs (Goldstein, DeBose-Boyd et al 2006). In monocytes and macrophages, ACAT1 expression was up-regulated by interferon γ and all-trans-retinoic acid via STAT1 (Yang, Duan et al 2001) and by dexamethasone via a glucocorticoid response element in its promoter (Yang, Yang et al 2004). ACAT1 has also been shown to have an NFκB binding element in its proximal promoter and to be upregulated in response to TNFα signaling through NFκB (Lei, Xiong et al 2009).…”
Section: Experimental and Mechanistic Evidence For Role Of Ldl In Cancermentioning
confidence: 99%